The relationship between performance in a theory of mind task and intrinsic functional connectivity in youth with early onset psychosis. (December 2019) - Ilzarbe, Daniel; de la Serna, Elena; Baeza, Inmaculada; Rosa, Mireia; Puig, Olga; Calvo, Anna; Masias, Mireia; Borras, Roger; Pariente, Jose C.; Castro-Fornieles, Josefina; Sugranyes, Gisela
Highlights: Youth with early-onset psychosis displayed deficits in theory of mind performance. They also showed reduced intrinsic connectivity in the medial prefrontal cortex. Differences in theory of mind were partially mediated by prefrontal connectivity. Both measures failed to show the age-positive associations observed in controls. Onset of psychosis in adolescence may impact development of social cognition. Abstract: Psychotic disorders are characterized by theory of mind (ToM) impairment. Although ToM undergoes maturational changes throughout adolescence, there is a lack of studies examining ToM performance and its brain functional correlates in individuals with an early onset of psychosis (EOP; onset prior to age 18), and its relationship with age. Twenty-seven individuals with EOP were compared with 41 healthy volunteers using the "Reading-the-Mind-in-the-Eyes" Test, as a measure of ToM performance. A resting-state functional MRI scan was also acquired, in which the default mode network was used to identify areas relevant to ToM processing employing independent component analysis. Group effects revealed worse ToM performance and less intrinsic functional connectivity in the medial prefrontal cortex in EOP relative to healthy volunteers. Group by age interaction revealed age-positive associations in ToM task performance and in intrinsic connectivity in the medial prefrontal cortex in healthy volunteers, which were not present in EOP. Differences in ToM performance were partially mediated by intrinsic functional connectivity in the medial prefrontal cortex. Poorer ToM performance in EOP, coupled with less medial prefrontal cortex connectivity, could be associated with the impact of psychosis during a critical period of development of the social brain, limiting normative age-related maturation.